Examining the Dynamics of Livelihood Strategies in Rural Thailand: A Case Study of Buriram, Sisaket, Chachoengsao, and Lopburi Provinces - Duangbootsee, Uchook (Asian Journal of Applied Economics, 2023)
Rural households in Thailand exhibit significant heterogeneity, necessitating tailored policy approaches to effectively reduce rural poverty. This study employs latent-class clustering and transition matrix analyses to classify and examine the dynamics of livelihood strategies among rural households. Using balanced-panel data from the Townsend Thai Project spanning the years 2000-2017, six distinct strategies are identified, with the three lowest-income strategies comprising 70.53% of the sample. These households share common characteristics, including limited farm diversification, with a primary focus on small-scale rice farming. Additionally, they often operate small businesses and find employment in low-wage jobs. Interestingly, these households demonstrate the highest level of mobility, particularly between low and medium livelihood strategies, throughout the study period. Conversely, households following high-income strategies engage in diverse income sources and possess higher levels of farm assets and education compared to those in poor-strategy households. Rural livelihood strategies exhibit considerable dynamism, with 39.86% of households transitioning to higher-ranked strategies at least once, and 24.15% descending to lower-ranked strategies over time. These transitions align with the prevailing economic context and government policies concerning agricultural price supports and micro-finance access. Policymakers should prioritize initiatives that promote farm diversification, strengthen farming and non-farming community networks, and mitigate fluctuations in farm prices. Moreover, rural development plans should consider tailored policies suitable for each livelihood strategy to enhance the efficiency and sustainability of programs.